The impact of self-congruity and virtual interactivity on online celebrity brand equity and fans' purchase intention. Issue 6 (29th June 2020) - Liu, Chengchen; Zhang, Ya; Zhang, Jing
Abstract : Purpose: There is growing interest among marketers in advertising and promoting their brands by adopting an online celebrity endorsement strategy. However, how online celebrities build their own brand equity and how online celebrity brand equity impacts fans' purchase behavior have not been extensively researched in the extant literature. This paper aims to explore the factors that contribute to online celebrity branding and improving fans' purchase intentions. Design/methodology/approach: A survey and an experiment were conducted among consumers from the mainland of China. A total of 12 hypotheses were proposed to exam how self-congruity and virtual interactivity impact online celebrity branding and to explore the moderating role of perceived quality and product type. Findings: This paper reveals that customers' perceived self-congruity with online celebrities' image and virtual interactivity positively impact the brand equity of online celebrities. Additionally, compared with virtual interactivity, the effect of customer perceived self-congruity on a brand is more significant. The brand equity of online celebrities thereby drives followers' purchase intentions and the perceived quality of products positively moderates this relationship. Originality/value: The research conclusions provide managerial implications for marketing practitioners for how to use human brands on social media platforms in the web 2.0 era and ultimately enhance consumer purchase intentions.